Pengaruh Pilates Exercise Terhadap Index Massa Tubuh Pada Anggota Gym Isometric Pilates Jakarta - WARDANI, Surti; , Umi Budi Rahayu, SSt. Ft. SPd. M. Kes; , Wahyuni, SSt.FT.M.Kes (2015)
Background : Physical Activity is one of the recommendations to address this issue, in a way that is easy and not very time consumig. Good physical activity used ti tackleexess body weight are by design to eliminate weight are by design to eliminate weight and fat content. One physical activity that can be used is a Pilates exercise that has six priciples of exercise. Objective : This study aimed in this research is to know the influence of pilates exercise with body mass index. Research method : This type of research is research observasional with designretropektif. The sample in research using a measurement tool for measuring weight and height while measuring teh BMI measurement using the parameters of the Departement of health Results : The results of comparative tests of paired samples t test get results on the effect of 0.05 p < Pilates exercise to changes in all categories of BMI. Conclusion: there are influences between pilates exercise with body mass index.